2022
DOI: 10.3390/app12136326
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nonsteroidal Anti-Inflammatory Drugs (NSAIDs) on Photosynthetic Parameters and Secondary Metabolites of Plants from Fabaceae Family

Abstract: Nonsteroidal anti-inflammatory medications (NSAIDs) are commonly used painkillers, anti-inflammatory agents, and fever reducers. They arrive in the environment from municipal wastewater and/or agriculture waste, affecting growing plants. In our study, the impact of NSAIDs, namely, diclofenac, indomethacin, naproxen, and paracetamol, on four plant species from the Fabaceae family (Cicer arietinum, Pisum sativum, Lens culinaris, and Vicia faba) was tested. The assimilation rate and stomatal conductance decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 67 publications
1
1
0
2
Order By: Relevance
“…In the case of high paracetamol concentrations, their inhibitory effect on the gas exchange rate of juvenile maize plants was confirmed. A similar conclusion was also confirmed for common bean plants [54]. A decrease in the rate of photosynthesis is associated with a reduced ability of the light reactions of photosynthesis.…”
Section: Discussionsupporting
confidence: 75%
“…In the case of high paracetamol concentrations, their inhibitory effect on the gas exchange rate of juvenile maize plants was confirmed. A similar conclusion was also confirmed for common bean plants [54]. A decrease in the rate of photosynthesis is associated with a reduced ability of the light reactions of photosynthesis.…”
Section: Discussionsupporting
confidence: 75%
“…In animal studies (male Wistar rats), an aqueous extract of tansy leaves has been shown to be nontoxic to the kidneys and to show no other side effects [94]. The content of active substances in the plant is most influenced by the anthropogenic environment [95][96][97][98], which is affected by animal husbandry [99], industry (pharmaceutical and medical [100,101], food, chemical and petroleum [102][103][104][105], etc. ), and wastewater [106][107][108][109][110].…”
Section: Introductionmentioning
confidence: 99%
“…Buna ek olarak; yeşil gübre olarak kullanımları ve havadaki serbest azotu (N) fikse edebilmeleri nedeniyle toprak yapısını iyileştirmektedirler. Son yıllarda, belirli sekonder metabolitler içermesi nedeniyle tıpta kullanımı artış göstermiştir [2][3][4].…”
Section: Introductionunclassified